Prognostic value of a left atrioventricular coupling index (LACI) in pre- and post-menopausal women. from the multi-ethnic study of atherosclerosis (MESA). (3rd October 2022) - Pezel, T; Michos, E D; Varadarajan, V; Shabani, M; Ambale Venkatesh, B; Vaidya, D; Kato, Y; De Vasconcellos, H; Heckbert, S; Wu, C; Post, W; Bluemke, D; et al.
Abstract: Background: Endogenous sex hormones associated with both the left atrial (LA) and left ventricular (LV) structures in peri-menopausal women, but the association of menopause status with left atrioventricular coupling is not well established. Purpose: To assess the prognostic value of a left atrioventricular coupling index (LACI) in pre- and post-menopausal women without a history of cardiovascular disease (CVD) at baseline in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: In women participating in the MESA study, the LACI was measured as the ratio of the left atrial (LA) end-diastolic volume to the left ventricular (LV) end-diastolic volume using cardiovascular magnetic resonance (CMR). Cox proportional hazard models were used to assess the association between the LACI and the outcomes of atrial fibrillation (AF), heart failure (HF), and hard CVD defined by myocardial infarction, resuscitated cardiac arrest, stroke, or coronary heart disease death. Results: Among the 2, 087 women participants (61±10 years), 485 cardiovascular events were observed during the mean follow-up period of 13.2±3.3 years. A higher LACI was independently associated with AF (HR 1.70; 95% CI [1.51–1.90]), HF (HR 1.62; [1.33–1.97]), and hard CVD (HR 1.30; [1.13–1.51], all p<0.001). Adjusted models with the LACI showed significant improvement in model discrimination and reclassification when compared to currently used standard models used to predict the incidence of AF (C-statistic=0.82 vs. 0.79; NRI=0.325; IDI=0.036), HF (C-statistic=0.84 vs. 0.81; NRI=0.571; IDI=0.023), hard CVD (C-statistic=0.78 vs. 0.76; NRI=0.229; IDI=0.012). Conclusion: In a multi-ethnic population of pre- and post-menopausal women, the LACI is an independent predictor of HF, AF, and hard CVD. In both pre- and post-menopausal women, the LACI has an incremental prognostic value for predicting cardiovascular events over traditional risk factors and sex hormone levels. ClinicalTrials: gov Identifier: NCT00005487 Funding Acknowledgement: Type of funding sources: None.